A simple fluorescence-based assay for quantification of the Toll-Like Receptor agonist E6020 in vaccine formulations. Issue 10 (7th March 2017) - Pollet, Jeroen; Versteeg, Leroy; Rezende, Wanderson; Strych, Ulrich; Gusovsky, Fabian; Hotez, Peter J.; Bottazzi, Maria Elena
Abstract: Despite the generally accepted immunostimulatory effect of Toll-Like Receptor 4 (TLR4) agonists and their value as vaccine adjuvants, there remains a demand for fast and easy quantification assays for these TLR4 agonists in order to accelerate and improve vaccine formulation studies. A new medium-throughput method was developed for the quantification of the TLR4 agonist, E6020, independent of the formulation composition. The assay uses a fluorescent hydrazide (DCCH) to label the synthetic lipopolysaccharide (LPS) analog E6020 through its diketone groups. This novel, low-cost, and fluorescence based assay may obviate the need for traditional approaches that primarily rely on Fourier transform infrared spectroscopy (FTIR) or mass spectrometry. The experiments were performed in a wide diversity of vaccine formulations containing E6020 to assess method robustness and accuracy. The assay was also expanded to evaluate the loading efficiency of E6020 in poly(lactic-co-glycolic acid) (PLGA) micro-particles.